The ellipse and the circle above intersect at and .
Let , where and are the areas of the ellipse and circle respectively.
If can be expressed as , where and are coprime positive integers, find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using a x 2 + b x y + c y 2 + d x + e y = 0 and the points I chose above to generate the ellipse.
(1) ( 0 , − 4 ) : 4 c − e = 0 ⟹ c = 4 e
(2) ( 8 , 4 ) : 1 6 a + 8 b + 4 c + 2 d + e = 0
(3) ( 8 , − 4 ) : 1 6 a − 8 b + 4 c + 2 d − e = 0
Subtracting (3) from (2) we obtain: 8 b + e = 0 ⟹ b = − 8 e
(4) ( 5 , 8 ) : 2 5 a + 4 0 b + 6 4 c + 5 d + 8 c = 0
Replacing c = 4 e and b = − 8 e into (2) and (4) ⟹
1 6 a + 2 d = − e
2 5 a + 5 d = − 1 9 e
⟹ a = 1 0 1 1 e and d = − 1 0 9 3 e
⟹ 1 0 1 1 x 2 − 8 1 x y + 4 1 y 2 − 1 0 9 3 x + y = 0 ⟹ 4 4 x 2 − 5 x y + 1 0 y 2 − 3 7 2 x + 4 0 y = 0 ⟹ 1 0 y 2 + 5 ( x − 8 ) y + 4 4 x 2 − 3 7 2 x = 0
Solving for y we obtain:
y = 4 x − 8 ± 2 0 1 3 4 7 5 2 2 0 7 7 4 4 − ( 3 4 7 x − 1 4 4 8 ) 2 .
y ( x ) = 4 x − 8 + 2 0 1 3 4 7 5 2 2 0 7 7 4 4 − ( 3 4 7 x − 1 4 4 8 ) 2 for the portion of the ellipse above the line y = 4 x − 8 .
Setting 2 2 0 7 7 4 4 − ( 3 4 7 x − 1 4 4 8 ) 2 = 0 ⟹ x = 3 4 7 1 4 4 8 ± 4 4 8 1 1 are the points of intersection of the ellipse and the line 4 x − 4 .
Letting a = 3 4 7 1 4 4 8 − 4 4 8 1 1 and b = 3 4 7 1 4 4 8 + 4 4 8 1 1 the area of the ellipse is A e = 2 ∫ a b y ( x ) − 4 x − 8 d x =
1 0 1 3 4 7 5 ∫ a b 2 2 0 7 7 4 4 − ( 3 4 7 x − 1 4 4 8 ) 2 d x = 2 5 3 4 7 1 ∫ a b 2 2 0 7 7 4 4 − ( 3 4 7 x − 1 4 4 8 ) 2 d x .
For I ( x ) = ∫ 2 2 0 7 7 4 4 − ( 3 4 7 x − 1 4 4 8 ) 2 d x
Let 3 4 7 x − 1 4 4 8 = 2 2 0 7 7 4 4 sin ( θ ) ⟹ d x = 3 4 7 2 2 0 7 7 4 4 cos ( θ )
⟹ I ( θ ) = 3 4 7 2 2 0 7 7 4 4 ∫ cos 2 ( θ ) d θ = 6 9 4 2 2 0 7 7 4 4 ∫ ( 1 + cos ( 2 θ ) ) d θ = 6 9 4 2 2 0 7 7 4 4 ( θ + sin ( θ ) cos ( θ ) )
⟹ I ( x ) = 6 9 4 2 2 0 7 7 4 4 ( arcsin ( 2 2 0 7 7 4 4 3 4 7 x − 1 4 4 8 ) + 2 2 0 7 7 4 4 3 4 7 x − 1 4 4 8 2 2 0 7 7 4 4 − ( 3 4 7 x − 1 4 4 8 ) 2 ) ⟹
A e = ( 3 4 7 ) 2 3 5 5 5 1 9 3 6 ( arcsin ( 2 2 0 7 7 4 4 3 4 7 x − 1 4 4 8 ) + 2 2 0 7 7 4 4 3 4 7 x − 1 4 4 8 2 2 0 7 7 4 4 − ( 3 4 7 x − 1 4 4 8 ) 2 ) ∣ a b = ( 3 4 7 ) 2 3 5 1 1 0 3 8 7 2 ( 2 π ) =
( 3 4 7 ) 2 3 5 5 5 1 9 3 6 π
For the circle ( x − x 0 ) 2 + ( y − y 0 ) = r 2 :
( 0 , 0 ) : x 0 2 + y 0 2 = r 2
( 0 , − 4 ) : x 0 2 + 1 6 + 8 y 0 + y 0 2 = r 2 ⟹ y 0 = − 2
( − 3 , 0 ) 9 + 6 x 0 + x 0 2 + y 0 2 = r 2 ⟹ x 0 = − 2 3
⟹ r 2 = 4 2 5 ⟹ A c = 4 2 5 π
⟹ A = A e − A c = ( ( 3 4 7 ) 2 3 5 5 5 1 9 3 6 − 4 2 5 ) π = ( ( 3 4 7 ) 2 3 5 ( 2 2 ) 5 ∗ 5 3 9 − ( 2 5 ) 2 ) π = ( ω α γ β ( α α ) β λ − ( α β ) α ) π ⟹ α + β + λ + γ + ω = 8 9 6 .